Analysis and Research on Transient Elasto hydrodynamic Lubrication of Gear Transmission - 卢立新; 付群峰; 蔡莹; 张和豪 (Jixie chuandong)
By considering the compressibility of lubricants,the influence of contact ratio on the loads of gear teeth,and the effects of variable curvature of tooth profile and sliding velocities,a group of equations of transient elasto hydrodynamic lubrication and a solution method are given in this paper.The pressure distribution and the form of oil film at the any point on the path of contact,and the variable curve of the thinnest oil film along the path of contact are also obtained by means of a full numerical solution based on the operating condition of the gear transmission.